Genomic and clinical characterization of HER2 exon 20 mutations in non-small cell lung cancer: insights from a multicenter study in South China - Yating Hou; Xingyang Xue; Zhuoyun Zhang; Dahai Mai; Wei Luo; Mingyu Zhou; Zichuan Liu; Yisheng Huang (BMC Cancer)
Abstract Background The objective of this study was to investigate the clinical and genetic characteristics and clinical relevance of HER2 exon 20 oncogenic variants in non-small cell lung cancer (NSCLC) patients. Methods This prospective study analyzed 51 NSCLC patients with HER2 mutations, identified via next-generation sequencing (NGS) of tissue, blood, cerebrospinal fluid, or pleural effusion samples. Patients were grouped based on the presence of exon 20 mutations (exon 20 vs. non-exon 20) and further divided based on whether they had received prior anti-tumor treatments (baseline vs. non-baseline). Clinical and genetic data, treatment responses were analyzed. Progression-free survival (PFS) and overall survival (OS) were evaluated using Kaplan-Meier methods and compared with log-rank tests. Gene ontology (GO) analysis was performed to uncover the biological significance of the mutated genes. Results In a cohort of 651 NSCLC patients, 51 (7.83%) harbored HER2 alterations, including 20 (3.08%) with exon 20 mutations. The median age of the HER2-altered subgroup was 58.5 years. Adenocarcinoma was the most prevalent subtype (96.1%), and most patients presented at stage IV (72.5%). The most common metastatic sites were the lungs (68.6%), lymph nodes (52.9%), and brain (43.1%). Among the HER2 mutated patients, 20 (39.3%) had exon 20 mutations. Exon 20 mutations were more prevalent in the non-baseline group (55.0% vs. 29.0%, P = 0.049) and males (75.0%, P = 0.025). These mutations were associated with a higher rate of metastasis to the lungs, lymph nodes (P < 0.001). Patients with exon 20 mutations demonstrated poorer overall survival (OS) outcomes (P = 0.048). No significant differences were observed in age, smoking history, histological subtype, or TNM stage at diagnosis between groups. The majority of exon 20 mutations were in-frame indel mutations (92.0%), with the most common specific mutation being p.Y772_A775dup (70%). Gene Ontology (GO) analysis linked exon 20 mutations to unregulated protein kinase activity and anoikis. Conclusions Our study found that NSCLC patients with HER2 exon 20 oncogenic variants have a higher risk of metastasis and drug resistance, leading to worse outcomes than non-exon 20 mutations. This highlights the urgent need for targeted therapies aimed at exon 20 insertions to improve survival and treatment outcomes in this subgroup.